THE TRADITION OF NEW PERSONALITY UPBRINGING IN THE HISTORY OF RUSSIAN EDUCATION - V. I. Polishchuk (Образование и наука)
The paper describes numerous attempts at upbringing the new personality undertaken in various periods of Russian history: the baptism of the Russian people by Prince Vladimir, reforms of Peter I concerning education and science, educational procedures introduced by Ekaterina II, etc. Each time, the governors wanted to see their people transformed and enlightened. The author analyzes the contribution of D. I. Mendeleyev to the national tradition of fostering the new personality; the scientist emphasized a priority of upbringing well-educated tutors who, in their turn, would educate a new breed of people. The Soviet time experience concerning education and upbringing of the future communism builders is revealed.Based on the retrospective analysis, the author comes to conclusion that all the unsuccessful attempts at upbringing the new personality resulted from the discrepancy between the officially stated goals and insufficient at-tempts to develop loyal and reliable citizens. Not enough emphasis was placed on the inner world of people compared to their words, deeds and attitudes. In author’s opinion, the actual renewal of people’s world outlook can be achieved only by getting rid of old misunderstandings and emphasizing the spiritual potential and existential bases.